Pengaruh Dukungan Sosial Keluarga terhadap Motivasi Belajar Siswa SMPN 05 Tangerang - Dendy Zaki Rahmad; Dimas Sukoco; Farhan Amamul Arifin (Asosiasi Ilmuwan Pendidikan, Sosial, dan Humaniora Indonesia, 2025)
Education plays a crucial role in shaping superior human resources, where learning motivation is the main factor in students' academic achievement. One of the external factors that contribute to learning motivation is family social support. This study aims to analyze the effect of family social support on the learning motivation of grade IX students at SMPN 5 Tangerang. A quantitative approach was used in this study with a survey method by distributing questionnaires to randomly selected respondents. The data obtained were analyzed using simple linear regression to test the relationship between the independent variables, namely family social support, and the dependent variable, namely student learning motivation. The results showed that there was a positive and significant relationship between family social support and student learning motivation. The most dominant forms of support in increasing learning motivation include emotional, financial, instrumental, and reward support. The implications of this study emphasize the importance of family involvement in the education process in order to increase student learning motivation. With optimal support from the family, students are expected to have a higher enthusiasm for learning and achieve better academic achievement.